2022
DOI: 10.1088/1748-3190/ac8e3e
|View full text |Cite
|
Sign up to set email alerts
|

Live fish learn to anticipate the movement of a fish-like robot *

Abstract: The ability of an individual to predict the outcome of actions of others and to change own behavior adaptively is called anticipation. There are many examples from mammalian species - including humans - that show anticipatory abilities in a social context, however, it is not clear to what extent fishes can anticipate the actions of their interaction partners and what are the underlying mechanisms for that anticipation. To answer these questions, we let live guppies (Poecilia reticulata) interact repeatedly wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Clonal Amazon mollies can learn in an operant conditioning paradigm within a few days and a low number of repeated training sessions to associate food with a location in their laboratory environments. This is in line with current research on fish cognition, which shows that fish are avid learners and have sophisticated cognitive abilities [Brown et al, 2008, Kohda et al, 2019, Bshary and Triki, 2022, Bierbach et al, 2022]. Further, Fuss and Witte [2019] and Fuss et al [2021] found similar learning capabilities in both parental species of the Amazon molly, P. latipinna and P. mexicana, and also in the closely related guppy ( P. reticulata ).…”
Section: Discussionsupporting
confidence: 88%
“…Clonal Amazon mollies can learn in an operant conditioning paradigm within a few days and a low number of repeated training sessions to associate food with a location in their laboratory environments. This is in line with current research on fish cognition, which shows that fish are avid learners and have sophisticated cognitive abilities [Brown et al, 2008, Kohda et al, 2019, Bshary and Triki, 2022, Bierbach et al, 2022]. Further, Fuss and Witte [2019] and Fuss et al [2021] found similar learning capabilities in both parental species of the Amazon molly, P. latipinna and P. mexicana, and also in the closely related guppy ( P. reticulata ).…”
Section: Discussionsupporting
confidence: 88%
“…Aside from using particle models and observation studies, robotic fish embedded within a school of fish are being used to observe and influence the behaviors of fish [44,45]. Researchers have demonstrated that the appearance and locomotion of a robot play crucial roles in its successful assimilation within a school of biological fish [46,47].…”
Section: Fish Behaviorsmentioning
confidence: 99%
“…At present, most studies choose collective parameters to analyze the interactive experimental results according to their experimental purpose. For example, the preference for robotic fish [11,20], time spent in robotic zone [14,17], probability of a collective avoidance and following [23], collective decision difference [2], the average angular distance used to characterize the different degree of individual distribution on the ring tank [9], and reaction time delay between robot and fish [22]. In this study, the collective parameters are put forward from two aspects: fish interaction proactivity and relative position relationship after interaction occurs.…”
Section: Collective Parametersmentioning
confidence: 99%
“…Considering that fish have a certain potential for learning [22], in order to limit the effect of fish learning on robotic fish behavior, at least 30 min apart between each set of trials, and no more than ten experiments were conducted each day. At the start of each experiment, we turned off the pool lights to minimize the presence of humans in the fish's sight, and gently placed the robotic fish in the pool to avoid stimulating fish.…”
Section: Experimental Settingmentioning
confidence: 99%
See 1 more Smart Citation